Structure dependent resistivity and dielectric characteristics of tantalum oxynitride thin films produced by magnetron sputtering - Cristea, D. (2015)
The main purpose of this work is to present and to interpret the change of electrical properties of TaxNyOzthin films, produced by DC reactive magnetron sputtering. Some parameters were varied during deposi-tion: the flow of the reactive gases mixture (N2and O2, with a constant concentration ratio of 17:3); thesubstrate voltage bias (grounded, −50 V or −100 V) and the substrate (glass, (1 0 0) Si or high speed steel).The obtained films exhibit significant differences. The variation of the deposition parameters inducesvariations of the composition, microstructure and morphology. These differences cause variation of theelectrical resistivity essentially correlated with the composition and structural changes. The gradualdecrease of the Ta concentration in the films induces amorphization and causes a raise of the resistivity.The dielectric characteristics of some of the high resistance TaxNyOzfilms were obtained in the sampleswith a capacitor-like design (deposited onto high speed steel, with gold pads deposited on the dielectricTaxNyOzfilms). Some of these films exhibited dielectric constant values higher than those reported forother tantalum based dielectric films.